Determinants of loan repayment performance: A study of microfinance institutions in Nepal - Lamichhane, Basu Dev; Bhaumik, Amiya; Gnawali, Achyut (Journal of Social Economics Research, 2024)
The study’s main goal is to empirically examine the association between loan repayment performance among microfinance institutions (MFIs) in Nepal regarding institutional characteristics (ICs), client characteristics (CCs), and loan characteristics (LCs). Further, the study emphasizes a causal relationship between the variables that directly corresponds with the regression research model for organic validity. For this, the researcher has chosen twenty Nepalese microfinance institutions along with 217 respondents for the study, respectively. The study found that institutional factors, client characteristics, and loan characteristics were positively and significantly associated with the loan repayment performance of Nepalese MFIs. The above-mentioned variables remain pivotal to determining the loan repayment performance of Nepalese MFIs, including institutional policy formation, loan and savings product design, and corporate culture formation for senior-level management. The results of the study will be effective for Banks and Financial Institutions (BFIs), Microfinance Institutions (MFIs), regulatory authorities, Human Resources (HR) analysts, and planners to take corrective actions to improve the repayment performance of MFIs for credit risk management.